The peptide secreted at the water to land transition in a model amphibian has antioxidant effects - Barbosa, Eder Alves; Plácido, Alexandra; Moreira, Daniel C.; Albuquerque, Lucas; Dematei, Anderson; Silva-Carvalho, Amandda É.; Cabral, Wanessa F.; Báo, Sonia N.; Saldanha-Araújo, Felipe; Kuckelhaus, Selma A. S.; Borges, Tatiana K.; Portugal, Camila C.; et al. (The Royal Society, 2021)
In addition to the morphophysiological changes experienced by amphibians during metamorphosis, they must also deal with a different set of environmental constraints when they shift from the water to the land. We found that Pithecopus azureus secretes a single peptide ([M + H]+ = 658.38 Da) at the developmental stage that precedes the onset of terrestrial behaviour. De novo peptide and cDNA sequencing revealed that the peptide, named PaT-2, is expressed in tandem and is a member of the tryptophyllins family. In silico studies allowed us to identify the position of reactive sites and infer possible antioxidant mechanisms of the compounds. Cell-based assays confirmed the predicted antioxidant activity in mammalian microglia and neuroblast cells. The potential neuroprotective effect of PaT-2 was further corroborated in FRET-based live cell imaging assays, where the peptide prevented lipopolysaccharide-induced ROS production and glutamate release in human microglia. In summary, PaT-2 is the first peptide expressed during the ontogeny of P. azureus, right before the metamorphosing froglet leaves the aquatic environment to occupy terrestrial habitats. The antioxidant activity of PaT-2, predicted by in silico analyses and confirmed by cell-based assays, might be relevant for the protection of the skin of P. azureus adults against increased O 2 levels and UV exposure on land compared with aquatic environments.
Keywords: Amphibia; antioxidant peptide; MALDI mass spectrometry imaging; oxidative stress; Pithecopus azureus; tryptophyllin